Accuracy of human epidermal growth factor receptor 2 (HER2) immunohistochemistry scoring by pathologists in breast cancer, including the HER2-low cutoff - Agata Wróbel; Michel Vandenberghe; Marietta Scott; Frances Jones; Tsuyoshi Matsuo; Anne-Marie Boothman; Jessica Whiteley; Craig Barker (Diagnostic Pathology)
Abstract Background Breast cancer was previously categorized as human epidermal growth factor receptor 2 (HER2)-positive (immunohistochemistry [IHC] 3+, IHC 2+ / in situ hybridization [ISH]–positive) or HER2-negative (IHC 0, IHC 1+, IHC 2+/ISH−). Recent studies of trastuzumab deruxtecan, a HER2-directed antibody-drug conjugate, have explored the spectrum of HER2 expression in tumors categorized as HER2-negative, including HER2-low (IHC 1+, IHC 2+/ISH−) and HER2-ultralow (IHC 0 with membrane staining). Clinical relevance of HER2-low and HER2-ultralow is reinforced by encouraging efficacy findings in these populations. Objective To assess HER2-low and HER2-ultralow scoring performance by pathologists, and compare real-world HER2-low scoring with centralized scoring by trained pathologists. Methods Formalin-fixed, paraffin-embedded breast cancer samples stained by the VENTANA anti-HER2/neu (4B5) Rabbit Monoclonal Primary Antibody (Roche) assay were selected to ensure adequate representation across all HER2 IHC scores (N = 500). Samples were rescored in a central laboratory by three pathologists trained in HER2-low scoring, and a majority consensus generated. Agreement between consensus and historical real-world HER2 scores was assessed by Fleiss’ kappa across HER2 scores (IHC 0, 1+, 2+, 3+). Results Substantial agreement was observed among central pathologists across HER2 scores (κ = 0.69), for the HER2-low cutoff (IHC 0 vs. IHC 1+, 2+, 3+; κ = 0.79), and the HER2-ultralow cutoff (IHC 0 absent membrane staining vs. IHC 0 with membrane staining, 1+, 2+, 3+; κ = 0.68). Substantial agreement was observed between real-world pathologists and central consensus for the HER2-low cutoff (κ = 0.72). Conclusions Pathologists can reproducibly score HER2-low and HER2-ultralow when supported by training. Findings may aid decision-making for patients with breast cancer who are potentially eligible for HER2-directed therapy.